The Constitutional Court's Purity as a Pillar of the Rule of Law - Chamicho, Putra Chinto; Hekar, Destito Kristian; Cahyani, Fhirza Sabhina (Jurnal Mengkaji Indonesia, 2024)
Abstract: The Constitutional Court has four primary areas of authority as stipulated in the 1945 Constitution, namely, reviewing legislation against the constitution, resolving disputes of authority among state institutions, dissolving political parties, and determining the results of general elections. Although the MK serves as the guardian and enforcer of the constitution, concerns have arisen that it may overstep its authority by acting as a positive legislator, a role that should be reserved for the legislative and executive branches. The importance of the separation of powers and a system of checks and balances is emphasized to prevent the MK from making unconstitutional decisions. Furthermore, the constitution should be understood as a living law within society, capable of evolving alongside social and political developments. Thus, the MK must adhere to its established authority to avoid disrupting the legal order and justice in Indonesia. This article aims to provide insight into the challenges faced by the MK in preserving the purity and integrity of Indonesia's legal system.